Added Value of CHA2DS2-VASc Score to Safe Contrast Volume for Contrast Induced Nephropathy Prediction after Percutaneous Coronary Intervention - Khalil, Wael Ali; Mohammad, Mohammad Gouda; Alshaer, Mohammad Hossam; Mageed, Mohammad Gamal Abd El (Jurnal Kardiologi Indonesia, 2025)
In “Added Value of CHA2DS2-VASc Score to Safe Contrast Volume for Contrast Induced Nephropathy Prediction after Percutaneous Coronary Intervention” (Indonesian Journal of Cardiology, 44(1), 1-9. https://doi.org/10.30701/ijc.1516), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1516. The error occurs only in the PDF; the DOI listed in the article metadata is already correct.The publisher apologizes for any inconvenience caused by this error. DOI of original article: https://doi.org/10.30701/ijc.1516